Legal Protection Assurance In Cryptocurrency Transactions - surono, surono; asriani, Asriani; Kumar, Prodip (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2022)
The purpose of this research is to analyze the law arising from crypto currency transactions in the form of bitcoin where the Bitcoin phenomenon causes several legal problems that are not yet clear on the regulation regarding the use and legal protection arising from the Bitcoin phenomenon. This research is included in normative or doctrinal legal research because this research uses positive norms in the legal system. The technique of data collection is done by literature study. The data analysis technique uses deductive logic by drawing conclusions from general problems to a concrete problem faced. Based on this research, the results show that although MUI has issued a fatwa on the prohibition of Cryptocurrency, Indonesia does not yet have a regulation on Bitcoin virtual currency. So that legal protection for users of this transaction does not obtain legal legal certainty from the State when there is a default or other unlawful act in the transaction